The Impact of Fear and Anti-Predator Behavior on the Dynamics of Stage-Structure Prey–Predator Model With a Harvesting - Majeed, Azhar Abbas (Iraqi Journal of Science, 2024)
In this paper, an ecological model with stage-structure in prey population, fear, anti-predator and harvesting are suggested. Lotka-Volterra and Holling type II functional responses have been assumed to describe the feeding processes . The local and global stability of steady points of this model are established. Finally, the global dynamics are studied numerically to investigate the influence of the parameters on the solutions of the system, especially the effect of fear and anti-predation.